2001
DOI: 10.1046/j.1440-1711.2001.01040.x
|View full text |Cite
|
Sign up to set email alerts
|

Changes in behaviour, cortisol and lymphocyte types during isolation and group confinement of sheep

Abstract: SummaryThis experiment compared changes in complex behaviour patterns, adrenal corticosteroid secretion and the numbers of various types of lymphocytes in sheep that were subjected to the stress of confinement. Grazing Merino ewes (n = 80 in five replicated experiments) were confined either in groups of four per pen or in total isolation from other sheep. The percentage of CD4 + lymphocytes increased while the percentage of CD8 + lymphocytes decreased over the experimental period. This result was more pronounc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
12
0
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(14 citation statements)
references
References 31 publications
1
12
0
1
Order By: Relevance
“…These findings suggest that offering concentrates may provide some level of immune protection, manifested as a lesser reduction in WC1+ (γδ T) cells and more stable αβ T cell population. An overall increase in CD4+: CD8+ ratio was reported by Degabriele and Fell (2001) [29] in sheep that were housed either in isolation or in groups. These authors attributed the rise in CD4+:CD8+ ratio to recovery of immune compensation following perturbation to lymphocyte subsets due to a stressful change in environment.…”
Section: Discussionsupporting
confidence: 59%
“…These findings suggest that offering concentrates may provide some level of immune protection, manifested as a lesser reduction in WC1+ (γδ T) cells and more stable αβ T cell population. An overall increase in CD4+: CD8+ ratio was reported by Degabriele and Fell (2001) [29] in sheep that were housed either in isolation or in groups. These authors attributed the rise in CD4+:CD8+ ratio to recovery of immune compensation following perturbation to lymphocyte subsets due to a stressful change in environment.…”
Section: Discussionsupporting
confidence: 59%
“…Group feeding of the forages was chosen to avoid the inevitable stress caused by individual confinement of lactating ewes in this long-term study (10 wk in total), whose goals were to evaluate production and immunological and hematological responses to feeds with high antioxidant activity. As individual confinement was reported to affect the immune system of sheep (Degabriele and Fell, 2001) and sheep are notoriously gregarious animals, in this experiment they were kept in groups to favor normal eating and social behaviors (Hutson, 2007).…”
Section: Resultsmentioning
confidence: 99%
“…This increase may reflect recovery of immune competence in an attempt to restore homeostasis following the initial reaction to the onset of stress. An overall rise in CD4 + : CD8 + ratio was reported in sheep that were housed either in isolation or in groups [47]. These authors attributed the rise in CD4 + :CD8 + ratio to recovery of immune compensation following perturbation to lymphocyte subsets due to a stressful change in the environment.…”
Section: Discussionmentioning
confidence: 97%
“…Decreases in both peripheral CD4 + and CD8 + lymphocytes have been reported in calves at unloading after 14 h truck transportation, following which they returned to pre-transport values by 24 h [14], and in beef steers following induction into a feedlot environment [43]. Some studies examining the effect of stress in domestic animals have utilised the CD4 + : CD8 + ratio as an indicator of stress-induced immunosuppression, however conflicting evidence exists in cattle [44-47]. Our findings showed that movement of beef calves from a pasture environment to a housing environment was able to elicit a transient increase in CD4 + :CD8 + ratio.…”
Section: Discussionmentioning
confidence: 99%